Does the Increase in the Cigarette Excise Tax Affect Cigarette Consumption? - Neni Susilawati; Daffa Abyan; Sabrina Cristalia Aruan; Marcel Angwyn (International Journal of Public Health Science (IJPHS), 2022)
The level of cigarette excise rates is one of the factors of cigarette costs. However, it is unclear how high the cigarette excise rate should be in order to reduce smoking in Indonesia. The aim of this research was to see how effective the cigarette excise tariff policy was at lowering public cigarette usage. The study conducted a quantitative approach, employing survey data collection techniques on a number of smokers as well as in-depth interviews. The data indicated that a 12.5% increase in the cigarette excise charge had a negligible effect on reducing cigarette consumption. The author identified numerous variables that contributed to the tobacco excise tax increase's ineffectiveness as a policy.